The Game-Changing Role of AI in Urban Development Decision-Making: Trends and Future Perspectives - Yehorchenkova, Nataliia; Yehorchenkov, Oleksii (AESOP, 2024)
Urban development in today's rapidly evolving landscape demands the integration of Artificial Intelligence (AI) to foster sustainable growth amidst vast spatial data. AI applications offer invaluable insights, revolutionizing decision-making processes by uncovering patterns, trends, and relationships. This paper explores the transformative potential of AI in urban development decision-making, highlighting trends, challenges, and future perspectives. Through advanced analytics and reporting tools, AI enables targeted interventions for environmental sustainability, resource optimization, and equitable social development. We delve into emerging trends such as Urban AI and synthetic data, examining their role in reshaping urban governance and planning. By addressing challenges and embracing innovative solutions, AI paves the way for sustainable, resilient, and inclusive urban futures.
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024